IDH1, ATRX, p53, and Ki67 Expression in Glioblastoma patients: Their Clinical and Prognostic Significance—A Prospective Study - Meel, Mukta; Jindal, Arpita; Kumar, Mukesh; Mathur, Kusum; Singh, Ashok (Asian Journal of Neurosurgery, 2024)
Context Glioblastoma multiforme (GBM) is a malignant and aggressive primary brain tumor with a poor prognosis. This adverse prognosis is due to the tumor's tendency for advancement and recurrence caused by highly intrusive nature of the persisting GBM cells that actively escape from the main tumor mass into the surrounding normal brain tissue. On the basis of biomarker illustration, it can be classified into molecular subgroups.Aims (1) To determine the expression of IDH1, ATRX, p53, and Ki67 by immunohistochemistry, in a cohort of GBMs. (2) To determine whether altered protein expression of any of these growth-control genes in GBM will show association with patient survival. (3) To establish prognostically distinct molecular subgroups of GBM, irrespective of histopathological diagnosis.Results In this prospective observational study, 35 histologically diagnosed cases of glioblastoma were enrolled. The mean age at the time of presentation was 43.46 ± 17.25 years with a male:female ratio of 1.3:1. Of the 35 cases, microvascular proliferation was seen in 23 cases. Large foci of necrosis (>50%) were seen in 10 cases and 27 cases had mitotic count ≥ 5/high power field (HPF). Of 35 cases, 5 (14.3%) cases showed IDH1 immunopositivity and 30 (85.7%) cases were negative for IDH1. ATRX was retained in 24 (68.6%) cases, while it was lost in 11 (31.4%) cases. The p53 immunoexpression was seen in 31 (88.6%) cases, whereas p53 was negative in 4 (11.4%) cases. The overall median survival (OS) was 6 months. In two protein pairs, the three compositions were IDH1–/p53+ (74.3%), ATRX +/IDH1– (62.9%), and ATRX +/p53+ (57.1%). Combined three-protein immunohistochemical analysis revealed five different molecular variants. Also, 8.6% (3/35) of the samples had aberrant protein expression of all three proteins, i.e., ATRX–/p53 +/IDH1 + , while 11.4% (4/35) were wild-type protein expression group, i.e., ATRX +/p53–/IDH1–.Conclusion In patients with single protein expression, Kaplan–Meier survival analysis showed statistically better OS in IDH1 mutant glioblastomas. In cases with double protein pairs, IDH1/p53 revealed statistically significant association with better median OS. The survival analysis of patients with IDH1/ATRX/p53 protein combinations also denoted a better OS. Hence, GBM can be grouped into prognostically relevant subgroups using these protein expression signatures individually, as well as the combined protein expression signatures.
Keywords: ATRX; glioblastoma; IDH1; overall survival